A Review of Investigations About Geometry Shape and Discharge Coefficient of Side Weirs - AL-Dulaimi, Mustafa Hussein Abed; Mohammed, Weam Abdulwahhab; Ghali, Zdainab Abdul sattar (International Journal of Psychosocial Rehabilitation, 2020)
The side weir is a hydraulic structure constructed longitudinally on the side of the main channel and is mainly used to reduce the flood wave and irrigate the lands. This study provides an overview of the side weirs and investigations about the geometry shape and discharge coefficient of the side weirs. The discharge coefficient equations depend mainly on the Froude number. Some dimensionless variables are used to study the discharge coefficient in conjunction with the Froude number, such as ratio side weir height to the head water on crest and the opening side weir length to the crest width . On the other hand, the length of the crest is considered a determinant for the selection of the side weir, where the dams with a long crest such as W shape, labyrinth and piano key side weir allow the passage of discharge through them higher than rectangular side weirs with (1.5-7.5) times.